Biochronology of North African small mammals - (:unkn) unknown (My University, 2014)
Throughout the late Cenozoic, climatic changes have strongly influenced the evolution of landscapes and faunas, especially terrestrial small vertebrates such as rodents and shrews. Compared to other regions, notably western Europe, few studies have been specifically dedicated to fossil small vertebrates in North Africa. However, several Neogene and Quaternary archaeological and paleontological sites from North Africa have yielded small vertebrate remains, allowing us to attempt a correlation between the evolution of small faunas and the global and more local environmental changes. The present paper aims to give a global synthesis on the biochronology and paleoecology of the North African small mammals, punctuated by specific examples. The North African faunas are of several origins, and display both African and Eurasian affinities, together with endemic taxa. The climatic changes and the opening or interruption of migration routes (through the Sahara, via the Straits of Gibraltar and Sicily or via the eastern Mediterranean), have highly influenced the arrival of new species or the isolation of local taxa leading to their extinction or adaptation, with different adaptative and time responses to environmental changes depending on the considered taxa.
Keywords: African Research